Developing of Learning Strategy PQ4R in Short Story Writing Learning - Siti Ansoriyah; Reni Oktaviani; Zahira Nur Arifah; Fani Kania (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of the study was to develop a PQ4R learning strategy for learning to write short stories for junior high school students in Jakarta. The method used R and D through the ADDIE model. Data were taken using observation, learning to write results and questionnaires. Data analysis was carried out through expert and peer assessment. The results of the study concluded that in the sixth step, discussion activities were added to discuss the results of short story writing and the peer assessment process. This strategy also had a positive impact on writing enthusiasm, increasing reading comprehension through reading activities in the third step. Students were also able to collaborate in developing short story writing. So, this research had implications for understanding the development of learning strategies that must be designed according to the character and needs of students and the learning objectives to be achieved. This model can be used in short story writing in class.